Urinary Exosomes. (2009) - Dimov, Irena; Jankovic Velickovic, Ljubinka; Stefanovic, Vladisav
Abstract : Exosomes are nanovesicles of endocytic origin that are secreted into the extracellular space or body fluids when a multivesicular body (MVB) fuses with the cell membrane. Interest in exosomes intensified after their description in antigen-presenting cells and the observation that they can significantly moderate immune responses in vivo . In the past few years, several groups have reported on the secretion of exosomes by almost all cell types in an organism. In addition to a common set of membrane and cytosolic molecules, exosomes harbor unique subsets of proteins, reflecting their cellular source. Major research efforts were put into their surprisingly various biological functions and in translating knowledge into clinical practice. Urine provides an exciting noninvasive alternative to blood or tissue samples as a potential source of disease biomarkers. Urinary exosomes (UE) became the subject of serious studies just a few years ago. A recent large-scale proteomics-based study of normal UE revealed a myriad of proteins, including disease-related gene products. Thus, UE have valuable potential as a source of biomarkers for early detection of various types of diseases, monitoring the disease evolution and/or response to therapy. As a relatively new field of research, it still faces many challenges, but UE have already shown some straightforward potential.